2022
DOI: 10.5194/nhess-22-1073-2022
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of two tsunamis generated by successive Mw 7.4 and Mw 8.1 earthquakes in the Kermadec Islands on 4 March 2021

Abstract: Abstract. On 4 March 2021, two tsunamigenic earthquakes (Mw 7.4 and Mw 8.1) occurred successively within 2 h in the Kermadec Islands, offshore New Zealand. We examined sea level records at tide gauges located at ∼100 to ∼2000 km from the epicenters, conducted Fourier and wavelet analyses as well as numerical modeling of both tsunamis. Fourier analyses indicated that the energy of the first tsunami is mainly distributed over the period range of 5–17 min, whereas it is 8–32 min for the second tsunami. Wavelet pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This possibility has not been achieved in our code yet. In addition, for tsunami earthquakes, the source has been modeled as a single fault plane, which is a common approach ( [36,37,40,63] among many others). However, a heterogeneous source consisting of a set of fault parameters, as done in reference [64] for instance, may be adequate if enough data is available.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility has not been achieved in our code yet. In addition, for tsunami earthquakes, the source has been modeled as a single fault plane, which is a common approach ( [36,37,40,63] among many others). However, a heterogeneous source consisting of a set of fault parameters, as done in reference [64] for instance, may be adequate if enough data is available.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain tsunami signals, we applied a high-pass lter with a cutoff frequency of 0.000069444 Hz (14400 s) to lter out the ocean tide from the original sea level records. This ltering approach has been employed in previous studies to extract observed tsunami waveforms (Cheng et al, 2023a, b;Heidarzadeh and Satake, 2013;Wang et al, 2022). For the analysis, we selected sea-level records from 06:00:00 UTC until 16:00:00 UTC on January 02, 2024, encompassing the period surrounding the January 2024 Noto earthquake at 07:10:09 (UTC).…”
Section: Tsunami Observationsmentioning
confidence: 99%
“…The Green's function is extracted from the stacked tsunami waveform data; in other words, we prepare an empirical Green's function (e.g., Y. Wang et al., 2022). We first confirm that the first seismic event Se01 did not produce measurable tsunami waves, but that the theoretical arrival times of the tsunamis caused by Se02 and Se03, agree well with the timings when the tsunami signal initiates (∼20:40) and when the amplitude increases (∼21:00), respectively (arrows in Figure 3a).…”
Section: Estimation Of Tsunami Source Time Functionmentioning
confidence: 99%